Climate Change and People Change: Dancing the Dialectic. Issue 2 (July 2017) - O'Keefe, Paul
The fifth assessment report of the Intergovernmental Panel on Climate Change (IPCC, 2014) says that accelerated climate change is occurring because of enhanced release of greenhouse gases. It is projected that temperatures will increase in East Africa but there is no agreement on how precipitation will change. There is acceptance that the climate system will throw up more frequent extreme conditions, including drought. We can begin to understand how this will materialize in people's livelihood strategies and adaptive choices. This paper identifies theoretical problems in the dominant discourses surrounding human-environment relations and climate change, and argues for a dialectical approach to the subject. It concludes with a brief vignette focused on a dialectical study of climate change.